SEJARAH DAN LITERATUR SUFI HEALING DALAM KHAZANAH ISLAM - Aminudin, Muhammad; Rusydi, Muhammad (Journal of Sufism and Psychotherapy, 2025)
This study examines Sufi healing in Islamic tradition as a psycho-spiritual healing system rooted in the teachings of the Prophet Muhammad ﷺ, the practices of the Companions, and the intellectual–spiritual development of classical Sufism. The research aims to explain the concepts, historical foundations, principles, methods, and contemporary relevance of Sufi healing for modern individuals who experience stress, anxiety, and meaning crises. Using a descriptive qualitative method through library research, this study analyzes classical Sufi texts, works of Islamic medicine, scholarly journals, and contemporary books, supported by hermeneutic analysis and source triangulation. The findings reveal that Sufi healing originated from prophetic practices such as ruqyah, supplication, and balanced living, and was later systematized by figures such as Ibn Sina, al-Razi, and al-Ghazali into a holistic healing paradigm that views humans as a unity of body, soul, and spirit. Its core principles include bodily–spiritual balance, tazkiyat al-nafs, remembrance (dhikr) as spiritual energy therapy, supplication and ruqyah, as well as meditation and contemplation (tafakkur). These principles manifest in practical methods such as dhikr jahr and khafi, sama’, qawwali, herbal remedies, and spiritual energy transfer practiced within various Sufi orders, including Mevlevi, Chishti, Qadiriyya, Naqshbandiyya, Sammaniyya, and Alawiyya. In the modern era, Sufi healing contributes significantly to Islamic psychotherapy, Islamic mindfulness, and holistic medicine by offering a comprehensive model that integrates medical, psychological, and theological dimensions, fostering inner tranquility, mental well-being, and spiritual closeness to Allah.